The Effects of Health, Labor and Capital towards Labor Productivity in Manufacturing Industries - Mohd Nor, Saffiah; Sahudin, Zahariah; Subramaniam, Geetha (Information Management and Business Review, 2023)
The manufacturing industry is the focus of this study, in which the proportion of its contribution to economic growth is experiencing a decreasing trend recently. Does it involve factors such as the input of capital, health, or workers that give significant impacts on labor productivity in the Malaysian manufacturing industry? This paper discovered the relationship between capital, health, and workers that consist of foreign and local labor with the labor productivity in the Malaysian manufacturing industry from 1986 to 2020. The Cobb-Douglas production function was used to derive the model specification in this study. The results showed that all variables are significant, in which capital and health have a positive relationship, whilst the factor of labor including local and foreign labor has a negative relationship with labor productivity. These findings may provide some insights into the improvement of manufacturing industries’ performance in Malaysia. It would be useful in determining which input factors significantly affected the productivity of manufacturing labor.